(Invited) Monolithic Integration of Si-CMOS and III-V-on-Si through Direct Wafer Bonding Process. (20th July 2018) - Lee, Kwang Hong; Zhang, Li; Wang, Bing; Wang, Yue; Sasangka, Wardhana; Lee, Kenneth E.; Fitzgerald, Eugene A.
Abstract : Integration of Si-CMOS and III-V compound semiconductors (with device structures of either InGaAs HEMT, InGaP LED, GaAs HBT, GaN HEMT or InGaN LED) on a common Si substrate is demonstrated. The Si-CMOS layer is temporarily bonded on a Si handle wafer. Another III-V/Si substrate is then bonded to the Si-CMOS containing handle wafer. Finally, the handle wafer is released to realize the Si-CMOS on III-V/Si substrate. For GaN LED or HEMT on Si substrate, additional wafer bonding step is required to replace the fragile Si (111) substrate after high temperature GaN growth with a new Si (001) wafer to improve the robustness of the GaN/Si wafers. Through this substrate replacement step, the bonded wafer pair can survive the subsequent processing steps. The monolithic integration of Si-CMOS + III-V devices on a common Si platform enables new generation of systems with more functionality, better energy efficiency, and smaller form factor.